Future bioenergy and sustainable land use - Schubert, Renate, 1955-; Wissenschaftlicher Beirat der Bundesregierung Globale Umweltveranderungen (Germany). (London : Earthscan, 2010)
'Because of the major opportunities and risks associated with it, and the complexity of the subject, bioenergy policy has in a short time become a challenging political task for regulators and planners - a task that can only be accomplished through worldwide cooperation and the creation of an international framework. WBGU's (German Advisory Council on Global Change) central message is that the sustainable potential of bioenergy, which can be tapped all over the world, should be utilized - provided that threats to sustainability are avoided. In particular, the use of bioenergy must not endanger food security or the goals of nature conservation and climate change mitigation.'--Publisher's description.
At head of title: German Advisory Council on Global Change.
Includes bibliographical references (p. [333]-359).
Translated from the German.
Keywords: Biomass energy; Biomass energy industries -- Environmental aspects; Land use -- Environmental aspects